Development of Teaching Problem Learning Model and Ability to Sharing Ability to Biological Competence Class VII Students of MTsN Pakan Rabaa - Yulia Ratna Sari; Yuni Ahda; Ramadhan Sumarmin (BIODIK, 2018)
The lack of student understanding on the topic of Biology presented by teacher may lead them towards a low achievement. This case could be seen from the low students’ average learning outcomes in the 7th grade Biology at MTsN Pakan Rabaa according to Minimum Completeness Criteria ( MCC ). One of the reasons is the traditional method of question and answer applied by the teachers. Biology teachers only emphasizes learning on cognitive aspects. The low level of student learning outcomes are also determined by the students’ prerequisite knowledge. In order to solve this problem, the use of Problem Based Learning and initial ability learning model was applied. The purpose of this study is to evaluate the effect of Problem Based Learning and Initial Ability learning models based on the competence of the student learning styles of 7th Grade Biology at MTsN Pakan Rabaa in 2014/2015 academic year. This research applied quasi experiment which used the static group comparison design. The population was all of the 7th grade MTsN Pakan Rabaa students in academic year of 2014/2015. Sampling technique used was saturated sampling technique and the participants for the experimental class were class VII A, with VII B as the control class. The research findings showed that (1) the students’ cognitive domain was significantly affected after the implementation of problem based learning model, except for those with high cognitive domain levels. (2) The students’ cognitive domain were improved significantly for both students with high and low ability. (3) The students’ psychomotor domain ability were improved significantly for both students with high and low ability (4) there was no interaction between the model of problem-based learning with the initial ability of students to learn biology cognitive competence of students.